Le tesi delle prime donne laureate a Firenze - Tagliabue, Floriana (Dialoghi con la società, 2022)
In Italy, women have been able to graduate only since 1875; in Florence, at the end of the century, just fifteen women obtained the graduation at the Institute of Higher Studies. The Libraries of the University of Florence, heirs to the Institute, have intended to celebrate those first female graduates (1875-1940) and their stories, by cataloguing, digitalizing and publishing online their thesis. The oldest or most significant ones, with archival materials, photos and publications, have been exhibited at the Humanities Library. This volume illustrates the exposition and the outcome of this original documentation, thus allowing to define the peculiarities of the Florentine reality, offering the opportunity for further studies and giving visibility to women who have played a substantial role in the Italian culture, so as to not lose their memory.